The Animal Question as Folklore in Science. - Barker, K. Brandon (Journal of Folklore Research)
Looking to answer ancient questions about the similarities and differences between humans and nonhuman animals, animal cognition scientists have deployed a traditional Aesopian fable, the Crow and the Pitcher, as narrative frame and structural precedent for experimental investigation. Herein, I consider the theoretical implications of this peculiar intersection between folklore and science in the contexts of Alan Dundes's notion of folk ideas (1971) and folkloristic genre theory. Ultimately, I gauge whether the so-called Aesop's Fable Paradigm is simply a folkloric cameo in science or a more complicated case of genuine scientific folklore.